Dual Inhibition of HIF-1α and HIF-2α as a Promising Treatment for VHL-Associated Hemangioblastomas: A Pilot Study Using Patient-Derived Primary Cell Cultures - Ana B. Perona-Moratalla; Blanca Carrión; Karina Villar Gómez de las Heras; Lourdes Arias-Salazar; Blanca Yélamos-Sanz; Tomás Segura; Gemma Serrano-Heras (Biomedicines)
Background: Von Hippel-Lindau (VHL) disease, a hereditary cancer syndrome, is characterized by mutations in the VHL gene, which result in the stabilization of hypoxia-inducible factors (HIF)-1α and -2α, ultimately leading to the development of highly vascularized tumors, such as hemangioblastomas of the central nervous system (CNS-HBs). The standard treatment for these brain tumors is neurosurgical resection. However, multiple surgeries are often necessary due to tumor recurrence, which increases the risk of neurological sequelae. Thus, elucidation of the proliferative behavior of hemangioblastomas (with the aim of identifying biomarkers associated with tumor progression) and the development of pharmacological therapies could reduce the need for repeated surgical interventions and provide alternative treatment options for unresectable CNS-HBs. Belzutifan (Welireg™), a selective HIF-2α inhibitor and the only FDA-approved non-surgical option, has shown limited efficacy in CNS-HBs, highlighting the need for alternative therapeutic strategies. Results: In this study, primary cell cultures were successfully established from CNS-HB tissue samples of VHL patients, achieving a 75% success rate. These cultures were predominantly composed of stromal cells and pericytes. The proliferative patterns of patient-derived HB cell cultures significantly correlated with tumor burden and recurrence in VHL patients. Furthermore, flow cytometry, reverse transcription-PCR, and Western blot analyses revealed marked overexpression of both HIF-1α and HIF-2α isoforms in primary HB cells. In addition, evaluation of the therapeutic potential of acriflavine, a dual HIF-1α/HIF-2α inhibitor, demonstrated reduced HB cells viability, induced G2/M cell cycle arrest, and predominantly triggered necrotic cell death in patient-derived HB cultures. Conclusions: These results suggest that the in vitro proliferative dynamics of HB cell cultures may reflect clinical characteristics associated with CNS-HB progression, potentially serving as indicators to predict tumor development in patients with VHL. Furthermore, our findings support the simultaneous targeting of both HIF-1α and HIF-2α isoforms as a promising non-invasive therapeutic strategy.